Amorphous carbon engineering of hierarchical carbonaceous nanocomposites toward boosted dielectric polarization for electromagnetic wave absorption. (5th January 2023) - Ban, Qingfu; Li, Yan; Li, Luwei; Qin, Yusheng; Zheng, Yaochen; Liu, Huimin; Kong, Jie
Abstract: Graphitic carbon materials are considered to be an important category of dielectric absorbers, but these materials are typically accompanied with poor impedance matching and unsatisfactory electromagnetic wave absorption (EMA) performance. Herein, engineered amorphous carbon is developed to produce hierarchical carbonaceous nanocomposites (HCNs) via crystallization-induced interfacial polymer self-assembly and carbonization, which is aimed at boosting dielectric polarization for enhancing EMA capability. By optimizing the polymer precursor species, graphitic carbon matrix, and carbonization temperature, the hierarchical architecture and N-bonding configurations, containing pyridinic N, pyrrolic N, and graphitic N, can be regulated for polarization relaxation loss and conductive loss. In addition, multiple reflection and scattering behavior are also beneficial for increasing EMA capability. Compared with those of the pure graphitic carbon matrix and related HCNs, the minimum reflection loss (RLmin ) of MWCNTs coated with polyimide-derived amorphous carbon at 700 °C (MWCNT/C(PI-EDA)-700) is −45.7 dB at a matched thickness of 3.6 mm with a filler loading of only 5 wt%, and its effective absorption bandwidth (EAB, RLmin  < −10 dB) is 3.9 GHz. In summary, based on the systematic analysis of 16 carbonaceous absorbers, in this study, not only the intrinsic EMA mechanism of HCNs is revealed, but also new avenues for designing and fabricating high-efficiency dielectric absorbers are opened. Graphical abstract: Image 1